2018
DOI: 10.1364/oe.26.015632
|View full text |Cite
|
Sign up to set email alerts
|

Core position alignment in polymer optical waveguides fabricated using the Mosquito method

Abstract: We fabricate multimode polymer optical waveguides with circular graded-index (GI) cores which are aligned in parallel at desired positions using the Mosquito method. In the Mosquito method, three-dimensional wiring patterns can be formed with a simple process. However, the core position is likely to deviate from the designed position because of multiple fabrication factors. Hence, in this paper, the dominant parameters to influence on the core height in the cladding are investigated both theoretically and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…8 in addition to a plane 9 mm behind the needle back-side edge. We already simulated the side view cross-section using the COMSOL Multiphysics software in the same way [15], and showed that just after being dispensed, the core monomer ascends slightly in the cladding monomer and gradually descends after leaving the needle. The core monomer flow trajectory shown in Fig.…”
Section: Circularization Of Core Shapementioning
confidence: 99%
See 2 more Smart Citations
“…8 in addition to a plane 9 mm behind the needle back-side edge. We already simulated the side view cross-section using the COMSOL Multiphysics software in the same way [15], and showed that just after being dispensed, the core monomer ascends slightly in the cladding monomer and gradually descends after leaving the needle. The core monomer flow trajectory shown in Fig.…”
Section: Circularization Of Core Shapementioning
confidence: 99%
“…When the dispensing angle is 0°, the edge of the needle scrapes a dip into the top of the core area. After the core monomer exits the backside edge, it ascends along the edge of the needle because a lower pressure area exists just behind the needle [15]. However, the core monomer does not sufficiently ascend to fill the dip and thus, a heart-like shape remains.…”
Section: Circularization Of Core Shapementioning
confidence: 99%
See 1 more Smart Citation